Physical demands during 3×3 international male and female basketball games are partially impacted by competition phase but not game outcome - Davide Ferioli; Ermanno Rampinini; Daniele Conte; Diego Rucco; Marco Romagnoli; Aaron Scanlan (Termedia Publishing House, 2022)
Despite the increased popularity and number of international competitions for 3×3 basketball, the precise physical demands of this sport are not well described. Therefore, this study aimed to quantify the physical demands of 3×3 basketball games according to game outcome and competition phase. Following an observational design, video footage from 27 games were analysed from 104 international 3×3 basketball players (n = 52 male and n = 52 female players) belonging to 26 national teams (n = 13 male and n = 13 female teams) during the 2019 FIBA 3×3 World Cup. Manual frame-by-frame time-motion analyses were conducted to determine the relative frequency (n·min−1) and duration (% of live playing time) for several physical demand variables to make comparisons according to game outcome (win vs. loss) and competition phase (group games vs. finals games). Linear mixed models for repeated measures and effect size analyses revealed non-significant, trivial-small differences in physical demands between games that were won and lost. Regarding competition phase, male players completed more high-intensity activity (sprinting, high-intensity specific movements, and jumping) but spent a greater proportion of playing time jumping and performing recovery activities (standing/ walking) during finals games than group games (P < 0.05, small), while female players performed more low intensity activity (jogging and low-intensity specific movements) during group games than finals games (P < 0.05, small). These findings indicate that the physical capabilities of male and female 3×3 basketball players may not be the determining factor for team success in games and players can mostly maintain activity outputs across phases of tournament play conducted at the highest international standard.